Fake news y posverdad: relación con las redes sociales y fiabilidad de contenidos - Dra. Almudena BARRIENTOS-BÁEZ,Dr. David CALDEVILLA-DOMÍNGUEZ,Dra. Lyudmyla YEZERS´KA (Fonseca, Journal of Communication, 2023)
The ICTs and the interconnectivity that they have brought to society have caused social phenomena to spread across the globe at a rate that can only be described as viral. This further limits the time available to society for their understanding, to ponder them and, if necessary, stop them with measures born from the field of social science studies. This article has the objective of helping create a necessary critical mass of studies, through a review of the literature, to allow the formation of a basic understanding of the mechanisms that make the post-truth work, the way they work, the factors that make its success possible and, with all the necessary help, the measures that can hypothetically be adopted from civil society, the academic world and political powers to prevent groups that have been marginalized from democratic life for having values opposed to coexistence, from slipping through the cracks of the digital information system and imposing their agenda and prejudices to society as a whole.